2021
DOI: 10.1080/08998280.2021.1951096
|View full text |Cite
|
Sign up to set email alerts
|

Medical views on the death by crucifixion of Jesus Christ

Abstract: The death of Jesus Christ remains a pivotal moment in world history and a symbol of love, mercy, and courage across the globe. Yet for centuries, the manner of Jesus' death has remained a subject of controversy in academic and medical circles. Forensic pathologists and clinicians have argued for several hypotheses concerning Jesus' death, including pulmonary embolism, cardiac rupture, suspension trauma, asphyxiation, fatal stab wound, and shock. This article surveys a broad range of medical and other specialis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Nevertheless, recent authors have stated that asphyxiation has reached consensus status among medical authors as the cause of death in crucifixion (Bordes et al 2020; Habermas, Kopel, and Shaw 2021; Habermas and Shaw 2021; Ingham and Duhig 2022). For instance“This article surveys a broad range of medical specialist views regarding Jesus’ experience on the cross, concluding that asphyxiation or asphyxiation-dominant theories have emerged as the consensus position regarding the cause of Jesus’ death” (Habermas and Shaw 2021)…”
Section: A Recent Consensus?mentioning
confidence: 99%
See 4 more Smart Citations
“…Nevertheless, recent authors have stated that asphyxiation has reached consensus status among medical authors as the cause of death in crucifixion (Bordes et al 2020; Habermas, Kopel, and Shaw 2021; Habermas and Shaw 2021; Ingham and Duhig 2022). For instance“This article surveys a broad range of medical specialist views regarding Jesus’ experience on the cross, concluding that asphyxiation or asphyxiation-dominant theories have emerged as the consensus position regarding the cause of Jesus’ death” (Habermas and Shaw 2021)…”
Section: A Recent Consensus?mentioning
confidence: 99%
“…That article simply tallies results of a literature search that found that in 40 articles and books written by physicians proposing a specific cause of death in crucifixion, 28 (70%) stated that asphyxiation was the primary cause (Habermas, Kopel, and Shaw 2021, Table 1). A recent find of a 2nd century A.D. skeleton in England with a nail through a heel bone described as belonging to a crucifixion victim stated that death in crucifixion “was usually due to asphyxia as the chest muscles became exhausted…” (Ingham and Duhig 2022, 28)…”
Section: A Recent Consensus?mentioning
confidence: 99%
See 3 more Smart Citations